MAIJA EINFELDE’S SONATA-MEDITATION FOR VIOLA AND PIANO: THE INTENTION OF THE COMPOSER AND THE APPROACHES OF THE PERFORMERS (Mūzikas akadēmijas raksti, 2024)
Before Maija Einfelde gained world renown as a choir music composer in the second half of the 1990s, one of her favourite genres was the sonata for string instruments and piano. Of her works, the one that was recorded the most often was Sonata-Meditation (Sonāte meditācija) for viola and piano. Recordings of this work have been made over a long period of time – from the 1980s up until even 2014. What made this work so attractive to performers of various generations – both from Latvia and internationally? What is similar and different in their interpretations? Those are questions that motivated me to analyse Maija Einfelde’s Sonata-Meditation in this paper and, firstly, to better understand the composer’s intention with this work.